2018 worldwide survey of health-care providers caring for patients with narcolepsy: WSS narcolepsy task force - Rosenthal, Leon; Thorpy, Michael J; Nevsimalova, Sona; Mayer, Geert; Han, Fang; Dauvilliers, Yves (Sleep medicine, 2021)
BACKGROUND: There are limited data available on regional differences in the diagnosis and management of narcolepsy. In order to better understand worldwide trends in clinical assessment and management of narcolepsy, a survey of health-care providers was conducted by the World Sleep Society Narcolepsy task force. METHODS: A total of 146 surveys that included items on the diagnosis and management of narcolepsy were completed by practitioners representing 37 countries. RESULTS: Most of the participants were from Europe, North America, Oceania, Asia and Latin America. A consistent approach to applying the diagnostic criteria of Narcolepsy was documented with the exception of measurement of CSF hypocretin-1, which has limited availability. While the majority of practitioners (58%) reported not using the test, 1% indicated always evaluating CSF hypocretin-1 levels. There was much variability in the availability of currently recommended medications such as sodium oxybate and pitolisant; modafinil and antidepressants were the most commonly used medications. Amphetamines were unavailable in some countries. CONCLUSION: The results of the study highlight clinical and therapeutic realities confronted by worldwide physicians in the management of narcolepsy. While the diagnostic criteria of narcolepsy rely in part on the quantification of CSF hypocretin-1, few physicians reported having incorporated this test into their routine assessment of the condition. Regional differences in the management of narcolepsy appeared to be related to geographic availability and expense of the therapeutic agents.
Keywords: CSF hypocretin-1; Europe; Asia; Narcolepsy type-2; péče o pacienta; Narcolepsy—pharmacotherapy; lidé; polysomnografie; Evropa; orexiny; Polysomnography; Patient Care; North America; Orexins; Narcolepsy type-1; Severní Amerika; narkolepsie; Asie; Narcolepsy; MSLT; HLA DQB1∗0602; Humans